In the name of beauty - Rolston, Holmes, 1932-2025, speaker; Brady, Emily, speaker; Pascale Smeesters and Bau Dang, producer (Colorado State University. Libraries, 2019)
There is beauty in nature. Is anything there ugly? Those who claim a "positive aesthetics" find that, although there is local ugliness, in a more comprehensive view, such ugliness becomes beautiful also. The rotting carcass is soon recycled. Rolston finds that life persists in the midst of its perpetual perishing, and that is, over the centuries, a positive aesthetic. Brady prefers to recognize that death can be aesthetically ugly, and finds the bigger picture a scientific rather than an aesthetic account.
Au nom de la beauté
The video is extracted from "In the Name of Beauty: Au Nom de la Beauté," produced by Pascale Smeesters and Bau Dang in Belgium in 2019.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Rolston, Holmes, 1932-2025; Brady, Emily; positive aesthetics; beauty; ugliness in nature